Will the economy of Siberia grow by Tuva? A «New Industrialization» of Siberia and the problems of Tuvan economic development - Begzi, Alexander D. (The New Research of Tuva, 2011)
The article deals with the issues of realization of the strategy of socio-economic development of Siberia by 2020 in the Republic of Tyva and the problems of state support for socio-economic development of Tuva. It’s necessary to correct the strategic documents adopted in the republic and discuss them at the economic forum.